Potential for polyhydroxyalkanoates and policaprolactone copolymer use as tissue-engineered scaffolds in cardiovascular surgery - L. V. Antonova; M. V. Nasonova; Yu. A. Kudryavtseva; A. S. Golovkin (Бюллетень сибирской медицины, 2012)
The absence of reliably functioning small-diameter vascular grafts for coronary artery bypass graft surgery remains one of the most important issues of cardiovascular surgery. Tissue-engineered grafts have to be characterized by highly hemocompatible, biomechanical and biocompatible properties, be quickly biodegradable and have non-toxic degradation products. This article presents polyhydroxyalkanoate and policaprolactone main characteristics and evaluates their potential use as polymers for producing vascular grafts. Biocompatibility, good physical and mechanical properties of these polymers and their better performance in copolymer scaffolds were demonstrated.